PENERAPAN MODEL MIND MAPPING DALAM MENINGKATKAN HASIL BELAJAR GEOMETRI BANGUN DATAR PADA SISWA SEKOLAH DASAR - Wibowo, Sonny Ari; Riyadi, Riyadi; Matsuri, Matsuri (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2025)
Students' understanding of flat building geometry material at the elementary school level is still relatively low, so it is one of the crucial challenges in learning mathematics. One of the main causes of this condition is the use of an instructional approach that does not support visual learning needs and does not provide a space for active participation for students. This study aims to examine how effective the Mind Mapping learning model is in improving student learning outcomes in the material. This study used a quasi-experimental method with a nonequivalent posttest-only control group approach. The research subjects consisted of two classes IV from the school. The results of the study show that the implementation of Mind Mapping is significant in improving student learning outcomes. The average post-test score in the experimental group was higher than in the control group, and the distribution of student scores in the "excellent" and "good" categories was also more dominant in the group that participated in Mind Mapping-based learning. These findings indicate that the Mind Mapping model can be an alternative in strengthening students' conceptual understanding.